The Malaysian food crisis: the escalating price of rice in Malaysia / Siti Nurhidayah Hairuddin - Hairuddin, Siti Nurhidayah (2008)
The recent food crisis debate in this Asian region has focused on hike price of food especially rice. Cross‐country evidence of consumption and the scarcity are discussed. Impracticable of rice subsidies and price elasticity are also considered. Continued increase in food prices imposes a heavy burden on consumers since the world fuel price also react the same. Criticisms and comments were thrown as to argue the failure of Malaysia to be selfsufficient in rice. There is a need to work on the policies, agriculture sectors, from production, supply chain and consumption, making this grain cheaper and more attractive for consumption in this urbanizing country rather than trying to think about substitution toward rice. Boosting the Malaysian rice production is hoped to reduce the country's dependency on imported rice and next make the country completely self‐sufficient. Future prospects on food demand in Malaysia were then analyzed based on these elasticities and some policy implications were drawn with regards to food security and food safety in this country. Rice must be secured to forbid any disturbance to the consumers particularly to the nation as well. This study proves that rice is necessity goods in this country. Hence substitution to other sources of carbohydrates does not give significant impact to the price of rice and consumption pattern itself. Malaysia must make sure that national stock pile enough to cater the demand of rice thus to curb the rising price of rice.